Hijacking Bacterial Electron Transfer for Iron - Mediated Polymerisations - Bennett, Mechelle (2021)
Polymer synthesis offers a plethora of methods and techniques to develop diverse and functional materials for a variety of applications. Reversible Deactivation Radical Polymerisation (RDRP) methods are the most versatile methods of which, Atom Transfer Radical Polymerisation (ATRP) and Reversible Addition Fragmentation chain-Transfer (RAFT) are highly promising for applications which require control over polymer structure, whilst sustaining mild reaction conditions. In the emerging areas of bioenergy harvesting and self-healing systems, methods to generate engineered living materials (ELM)s and hybrid synthetic/natural superstructures are being considered. These might have applications in microbial fuel cells (MFC), biological sensing, bioreactors, bioremediation, or as implantable synthetic microbiomes.